Antibody-platinum (IV) prodrugs conjugates for targeted treatment of cutaneous squamous cell carcinoma - Xiangye Yin; Yingjie Zhuang; Haiqin Song; Yujian Xu; Fan Zhang; Jianxin Cui; Lei Zhao; Yingjie Yu; Qixu Zhang; Jun Ye; Youbai Chen; Yan Han (Elsevier, 2024)
Antibody-drug conjugates (ADCs) are a new type of targeting antibodies that conjugate with highly toxic anticancer drugs via chemical linkers to exert high specificity and efficient killing of tumor cells, thereby attracting considerable attention in precise oncology therapy. Cetuximab (Cet) is a typical antibody that offers the benefits of good targeting and safety for individuals with advanced and inoperable cutaneous squamous cell carcinoma (cSCC); however, its anti-tumor activity is limited to a single use. Cisplatin (CisPt) shows good curative effects; however, its adverse effects and non-tumor-targeting ability are major drawbacks. In this study, we designed and developed a new ADC based on a new cytotoxic platinum (IV) prodrug (C8Pt(IV)) and Cet. The so-called antibody-platinum (IV) prodrugs conjugates, named Cet-C8Pt(IV), showed excellent tumor targeting in cSCC. Specifically, it accurately delivered C8Pt(IV) into tumor cells to exert the combined anti-tumor effect of Cet and CisPt. Herein, metabolomic analysis showed that Cet-C8Pt(IV) promoted cellular apoptosis and increased DNA damage in cSCC cells by affecting the vitamin B6 metabolic pathway in tumor cells, thereby further enhancing the tumor-killing ability and providing a new strategy for clinical cancer treatment using antibody-platinum (IV) prodrugs conjugates.